TINDAK TUTUR EKSPRESIF PADA KOLOM KOMENTAR YOUTUBE ROCKY GERUNG “GUBERNUR NTT BIKIN HEBOH, PERINTAHKAN SISWA SMA MASUK JAM 5 PAGI. SALAH PAHAM DUNIA PENDIDIKAN” - Nabilah Syafendra; Fatmawati (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The tendency of someone to express expressive speech on social media is the background in this study. Many users express themselves by commenting on someone's account video uploads. The purpose of this study was to find out and understand the forms of expressive speech acts in the Rocky Gerung Youtube comments column entitled “The Governor of NTT Makes a Scene, Orders High School Students to Enter at 5 in the Morning. Misunderstanding of the World of Education”. The theory of expressive speech acts in this study is the combined theory of Searle, Nadar, Leech, and Tarigan. The approach in this research is a qualitative approach with content analysis method. The source of the data in this study is a comment on Rocky Gerung's Youtube